The effect of speed, power, and strength training and a group motivational presentation on physiological markers of athlete readiness: a case study in professional rugby - Serpell, B. G.; Strahorn, J.; Colomer, C.; McKune, A.; Cook, C.; Pumpa, K. (International Journal of Sports Physiology and Performance, 2019)
Objective: To examine the effect of a physical treatment (speed, power, and strength [SPS] training) and psychosocial treatment (group motivational presentation) on salivary testosterone (sal-T), salivary cortisol (sal-C), and sal-T-to-sal-C ratio (T:C) in professional rugby. Methods: Fourteen male rugby players (age = 25.9 [2.5] y, height = 186.1 [6.7] cm, and body mass = 104.1 [12.7] kg) participated in this study. Testing occurred across 2 d on 2 separate occasions (week 1 and week 2). On day 1 of both weeks, participants completed an SPS training session. On day 2 of both weeks, participants undertook a field-based rugby training session. In week 2, participants underwent an additional treatment in the form of a motivational presentation given by a respected former player before the rugby session. Saliva was collected before and after SPS training and before and after the rugby session and was assayed for testosterone and cortisol. Results: No differences were found between weeks for sal-T at any time point, but sal-C was higher in week 2 before and after SPS and before rugby on day 2 (P < .05). In both weeks, T:C increased following SPS (P < .02, ES > 0.91 [0.13, 1.69]). T:C increased when the motivational presentation accompanied rugby training (P = .07, ES = 1.06 [0.27, 1.85]). Sal-C, not sal-T, drove changes in T:C (P < .001). Conclusions: Physical or psychosocial treatments may affect sal-T, sal-C, and T:C, and individual variation in responses to treatments may exist.